(untitled) (Rockland, MA., 2006)
Skype Me! provides readers with a complete understanding of the technology behind Skype, walks through the steps for getting connected quickly, and then provides IT professionals with instructions on deploying and securing Skype in the workplace.
Keywords: Internet telephony.,Internetworking (telecommunication).,Điện thoại Internet,Liên mạng viễn thông